Cities and sustainable technology transitions. Leadership, innovation and adoption. - (:unkn) unknown (Elgar, 2018)
Cities are undoubted key players in technology creation and adoption for sustainable transitions. The book addresses both the active and passive roles of cities in technology innovation, commercialisation, mass-production and adoption. In particular, it examines elements of three socio-technical systems, energy, transport and healthcare. The authors investigate cities in Europe, Asia and North America, providing an in depth understanding of the differences in leadership roles that cities adopt across the globe. The book breaks new ground in the analysis of topical issues such as local 'cradle' conditions, incentive schemes, niche-development, living labs, impact bonds, grass-roots intermediation and adaptive policy making.
Keywords: Stadtentwicklungsplanung; Technische Infrastruktur; Innovation; Energiesystem; Verkehrssystem; Gesundheitswesen; Wissenschaft; Hochschule; Urban Governance; Stadtsystem; Stadttechnik; Netzwerk; Steuerung; Nachhaltige Entwicklung; Erneuerbare Energie; Medizintechnik; Brennstoffzelle